Determining the Ages of Nearby A-Stars with Long-Baseline Interferometry. Issue Volume 10:Issue S314(2015) (November 2015) - Jones, Jeremy; White, R. J.; Boyajian, T.; Schaefer, G.; Baines, E.; Ireland, M.; Patience, J.; ,
Abstract: We determine the age of 7 stars in the Ursa Major moving group using a novel method that models the fundamental parameters of rapidly rotating A-stars based on interferometric observations and literature photometry and compares these parameters (namely, radius, luminosity, and rotation velocity) with evolution models that account for rotation. We find these stars to be coeval, thus providing an age estimate for the moving group and validating this technique. With this technique validated, we determine the age of the rapidly rotating, directly imaged planet host star, κ Andromedae.